UPAYA MANAJEMEN PEMERINTAHAN DESA DALAM MENINGKATKAN PRODUKTIVITAS BUMDES SEBAGAI PENGUAT EKONOMI DI DESA CIKALONG KECAMATAN CILAMAYA WETAN - Hudan Praidna Anwar; Evi Priyanti (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
Even though every village in Indonesia, especially in Karawang, has its own potential, especially Karawang, whose geographical conditions are very favorable, such as the sea, hills and forests, making Karawang even richer in natural resources, not to mention its location. close to anywhere like close to the capital. In my opinion, Cikalong Village, Cilamaya Wetan District, has a lot of potential that can be utilized. BUMDes in the implementation and ownership of capital are managed by the village government and the community. Gunawan (2011) explains the formation of BUMDes aims to receive activities that develop according to customs, activities based on government programs and all other activities that support efforts to increase people's income. This research uses descriptive qualitative method. According to Sugiono, qualitative research is research where researchers are placed as key instruments, data collection techniques are carried out in combination and data analysis is inductive (Sugiono. 2010: 9). This data collection technique used interviews, observation and documentation, researchers took 5 samples to be interviewed. The results of this study are that BUMDes in Cikalong village have not run optimally and their improvements are still lacking, so that BUMDes have not become an economic support for the people of Cikalong Village, Cilamaya Wetan District.